A Boarding School Santri Supervision System Design Based on Android Application to Replace the Rule of Dormitory Supervisor - Mochammad Taufik; Najibur Rohman; Hudiono Hudiono (Jurnal Jaringan Telekomunikasi, 2022)
An Islamic educational facility called a pesantren houses students, or santri, in dormitories. One of the biggest Islamic boarding schools in Jombang is called Darul 'Ulum. Students are expected to participate in early recitation activities, are forbidden from smoking, are forbidden from visiting the student rooms without the coach's permission, and are forbidden from entering the guest rooms. This research used a case study of a high school dormitory as an example. For proper monitoring of student breaches, a high number of students demand more efficient supervision. Based on these issues, a monitoring system is required that may alert the hostel supervisor to infractions in real-time, allowing them to take fast action against violators and impose sanctions in line with the seriousness of the offenses. This study uses an android application monitoring of students. According to the results of testing violations of students who smoke in the room using the MQ-2 sensor with 10 test trials, a 100% success rate is obtained in detecting cigarette smoke, and testing violations of students who are still in the room at the time of the early Koran reading with using a PIR sensor with 10 test trials, the success rate was 100% in detecting the presence of students. Both the RFID sensor test and the fingerprint sensor test resulted in delays of 1.59 seconds and 3.01 seconds, respectively, with 100% success rates.